Use of Salmonella Bacteria in Cancer Therapy: Direct, Drug Delivery and Combination Approaches - Badie, Fereshteh; Ghandali, Maryam; Tabatabaei, Seyed Alireza; Safari, Mahmood; Khorshidi, Ahmad; Shayestehpour, Mohammad; Mahjoubin-Tehran, Maryam; Morshedi, Korosh; Jalili, Amin; Tajiknia, Vida; Hamblin, Michael R.; Mirzaei, Hamed (Frontiers in Oncology, 2021)
Over the years, conventional cancer treatments, such as chemotherapy with only a limited specificity for tumors, have undergone significant improvement. Moreover, newer therapies such as immunotherapy have undergone a revolution to stimulate the innate as well as adaptive immune responses against the tumor. However, it has been found that tumors can be selectively colonized by certain bacteria, where they can proliferate, and exert direct oncolytic effects as well as stimulating the immune system. Bacterial-mediated cancer therapy (BMCT) is now one example of a hot topic in the antitumor field. Salmonella typhimurium is a Gram-negative species that generally causes self-limiting gastroenteritis in humans. This species has been designed and engineered in order to be used in cancer-targeted therapeutics. S. typhimurium can be used in combination with other treatments such as chemotherapy or radiotherapy for synergistic modification of the tumor microenvironment. Considerable benefits have been shown by using engineered attenuated strains for the diagnosis and treatment of tumors. Some of these treatment approaches have received FDA approval for early-phase clinical trials. This review summarizes the use of Salmonella bacteria for cancer therapy, which could pave the way towards routine clinical application. The benefits of this therapy include an automatic self-targeting ability, and the possibility of genetic manipulation to produce newly engineered attenuated strains. Nevertheless, Salmonella-mediated anticancer therapy has not yet been clinically established, and requires more research before its use in cancer treatment.